Novel antiseptic compound OPB-2045G shows potent bactericidal activity against methicillin-resistant Staphylococcus aureus and vancomycin-resistant Enterococcus both in vitro and in vivo: a pilot study in animals. Issue 1 (January 2015) - Inoue, Yasuhide; Hagi, Akifumi; Nii, Takuya; Tsubotani, Yoshie; Nakata, Hikaru; Iwata, Koushi
Abstract : There is a need for new compounds to effectively treat methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus (VRE). The novel monobiguanide compound 1-(3, 4-dichlorobenzyl)-5-octylbiguanide gluconate (OPB-2045G) has potential bactericidal activity. We sought to elucidate the potency of OPB-2045G bactericidal activity against MRSA and VRE compared to those of chlorhexidine digluconate (CHG) and povidone iodine (PVP-I). In vitro bactericidal activity was analysed using minimum bactericidal concentration (MBC) as the index. The in vivo bactericidal efficacy of OPB-2045G was examined by determining MRSA and VRE contamination of the normal dorsal skin of mice following removal of hair. After a 3 min treatment period, the MBC of OPB-2045G was lower than that of CHG and PVP-I against standard strains and clinical isolates. Additionally, in our in vivo mouse model, the in vivo bactericidal activity of 1.5 % OPB-2045G (a clinically relevant dose) was higher than that of 0.5 % CHG and equivalent to that of 10 % PVP-I against MRSA. Similarly, the in vivo bactericidal activity of OPB-2045G was higher than that of 0.5 % CHG and 10 % PVP-I against VRE. OPB-2045G showed more potent bactericidal activity against MRSA and VRE both in vitro and in vivo compared to CHG and PVP-I, indicating that OPB-2045G may provide better protection against health care-associated infections caused by these pathogens. Abbreviations: CHG, chlorhexidine digluconate; MBC, minimum bactericidal concentration; MRSA, methicillin-resistant Staphylococcus aureus ; OPB-2045, 1-(3, 4-dichlorobenzyl)-5-octylbiguanide; OPB-2045G, 1-(3, 4-dichlorobenzyl)-5-octylbiguanide gluconate; PVP-I, povidone iodine; SCDLP, soybean–casein lecithin polysorbate; VRE, vancomycin-resistant Enterococcus .